Śri 5 Mahārājādhirāja Vīrendra Vīra Vikrama Śāha Devabāṭa baksekā ghoshaṇā, bhāshaṇa, ra sandeśaharū, 2028-2032 - Birendra Bir Bikram Shah Deva, King of Nepal
Royal proclamations, speeches, and messages, 1972-1975.